2001
DOI: 10.1074/jbc.m007753200
|View full text |Cite
|
Sign up to set email alerts
|

p21-activated Protein Kinase γ-PAK Suppresses Programmed Cell Death of BALB3T3 Fibroblasts

Abstract: In response to stress stimulants, cells activate opposing signaling pathways for cell survival and programmed cell death. p21-activated protein kinase ␥-PAK is involved in both cell survival and cell death pathways. Many stress stimulants activate ␥-PAK as a full-length enzyme and as a proteolytic fragment. Caspase-mediated proteolytic activation parallels cell death and appears to be a pro-apoptotic factor in stress-induced cell death. Here, we show that activation of full-length ␥-PAK promotes cell survival … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
84
2

Year Published

2002
2002
2015
2015

Publication Types

Select...
8
1
1

Relationship

0
10

Authors

Journals

citations
Cited by 109 publications
(87 citation statements)
references
References 46 publications
1
84
2
Order By: Relevance
“…Caspase-3-mediated cleavage of PAK2 has been observed during apoptosis (15,25,26), and overexpression of the Nterminally tagged C-terminal cleavage product C-t-PAK2 has been shown to induce cell death (16,24,27). However, all these previous studies assessed the apoptotic activity of the nonphysiologically relevant, nonmyristoylated form of C-t-PAK2.…”
Section: Resultsmentioning
confidence: 90%
“…Caspase-3-mediated cleavage of PAK2 has been observed during apoptosis (15,25,26), and overexpression of the Nterminally tagged C-terminal cleavage product C-t-PAK2 has been shown to induce cell death (16,24,27). However, all these previous studies assessed the apoptotic activity of the nonphysiologically relevant, nonmyristoylated form of C-t-PAK2.…”
Section: Resultsmentioning
confidence: 90%
“…A previous study has shown that Pak2 phosphorylates Bad at Ser-112 and Ser-136 and inhibits the pro-apoptotic activity by preventing heterodimerization with Bcl-2, and Bcl-Xl [18]. Additionally, Jakobi et al in their study found that Pak2 gene suppressed programmed cell death of BALB3T3 fibroblasts by phosphorylating Bad at Ser-112 and Ser-136 [19]. So in our study we researched if miR-134 inhibiting cell proliferation and promoting cell apoptosis by regulating Pak2 gene and after that affect bcl-2 family member Bad by phosphorylation of Bad at Ser-112 and Ser-136.…”
Section: Mir-134 Enhanced Paclitaxel-sensitivity and Induces Apoptosimentioning
confidence: 97%
“…The effects of US3 on the actin cytoskeleton have recently been attributed to an interaction of US3 with p21-activated kinases (PAKs) 1 and 2, and extracellular PRV virus titres were reduced in PAK2 2/2 cells (Van den Broeke et al, 2009b). Interestingly, PAKs are not only involved in rearrangements of the actin cytoskeleton, but also in anti-apoptotic effects (Cotteret et al, 2003;Gnesutta et al, 2001;Jakobi et al, 2001;Rudel & Bokoch, 1997;Schurmann et al, 2000;Tang et al, 2000). Based on our current study, we hypothesize that the reduced PRV titres on PAK2 2/2 cells are probably due to the effect of PAK2 on the actin cytoskeleton, rather than the effect of PAK2 on apoptosis.…”
mentioning
confidence: 99%